The THE RELATIONSHIP BETWEEN KNOWLEDGE AND ADHERENCE OF BLOOD SUPPLEMENTED TO THE INCIDENCE OF ANEMIA IN PREGNANT AND LACTATING WOMEN IN PALU CITY: Indonesia - Parumpu, Firdawati; Rumi, Amelia; Putri, Amanda (Acta Pharmaceutica Indonesia, 2024)
Anemia is one of the conditions that often occurs in pregnant and lactating women when hemoglobin levels in the body are below normal, therefore pregnant and lactating women are strongly encouraged to take Blood Supplemented during pregnancy and lactation. This study was conducted to determine the incidence of anemia, the level of knowledge of respondents, the level of compliance of respondents, and to determine the effect of the level of knowledge and compliance on the incidence of anemia in pregnant and lactating women in Palu City. This research method uses a cross sectional design with accidental sampling technique by giving questionnaires to respondents. The results obtained were that the level of knowledge of respondents in the good category obtained a greater percentage of 63%, the level of compliance of respondents in the low category of 37%, and the level of anemia incidence in respondents obtained anemia respondents as much as 60%. The results of the chi-square test on compliance obtained a sig probability value ≤ 10% (0.1) P-value of 0.000, while the knowledge obtained a value of 0.103. The conclusion of this study is that there are many respondents who are anemic, at the level of knowledge obtained in the good category, while at the level of compliance the respondents are said to be low, so there is a relationship between the level of compliance of respondents to the incidence of anemia in pregnant and lactating women in Palu City.